COQ8B glomerular nephropathy: Outcomes after kidney transplantation and analysis of characteristics in Chinese population - Zeng, Shuhan; Xu, Yuanyuan; Cheng, Cheng; Yu, Nannan; Liu, Longshan; Mo, Ying; Chen, Lizhi; Jiang, Xiaoyun (Frontiers in Pediatrics, 2022)
Background: Mutation in the COQ8B gene can cause COQ8B glomerular nephropathy (COQ8B-GN),which is rare and associated with steroid-resistant nephrotic syndrome (SRNS) as well as rapid progression to end-stage renal disease (ESRD).The aim of present study was to analyze the prognosis and recurrence risk of COQ8B-GN in patients after kidney transplantation(KTx) and summarize the characteristics in Chinese population. Methods: A retrospective study included four cases treated in our hospital with a diagnosis of COQ8B-GN.Chinese and foreign literatures were searched from database inception to February 2022. Results: Four cases were included with age of onset ranging from 4 to 9 years old.The initial presentations were SRNS and asymptomatic proteinuria.Only one had extrarenal manifestation(thyroid cyst). All patients progressed to ESRD at a mean time of 42 months after onset.Three of them had received transplantation with total follow-up time ranged from 12 to 87 months.Two recipients had excellent graft function while one case needed a second KTx due to graft failure caused by chronic rejection. No recurrence in allograft was observed.18 cases in KTx recipients has been reported globally with follow-up information.Except for two cases of graft failure caused by hyperacute rejection and chronic rejection respectively, the rest all had good graft function without recurrence.In addition,44 cases of COQ8B-GN in Chinese population were identified.75% of the patients at onset was ≤10 years old with initial symptoms of asymptomatic proteinuria,nephrotic syndrome(NS) or SRNS.59% patients had progressed to ESRD by the time of literature publication(mean age of 10.3±3.6 years). The median time from onset to ESRD was 21 months.Renal pathology mainly showed focal segmental glomerulosclerosis(FSGS),accounting for 61.8% of all biopsies,followed by mesangial proliferative glomerulonephritis（20.6%）.The first three prevalent mutation in COQ8B gene among Chinese population were c.748G>C,c. 737G>A and c. 532C>T. Conclusions: COQ8B-GN in Chinese population may present with asymptomatic proteinuria,NS or SRNS initially with most onset before 10 years old.A lot patients progressed to ESRD in early adolescence. FSGS on biopsy and c.748G>C in genetic test are the most frequently seen in Chinese COQ8B-GN patients.KTx is feasible for patients with ESRD due to low risk of recurrence,but we should pay attention to graft rejection.